2013
DOI: 10.1242/dev.087940
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of polarity in 3D reveals local cell coordination in the embryonic mouse heart

Abstract: Anisotropies that underlie organ morphogenesis have been quantified in 2D, taking advantage of a reference axis. However, morphogenesis is a 3D process and it remains a challenge to analyze cell polarities in 3D. Here, we have designed a novel procedure that integrates multidisciplinary tools, including image segmentation, statistical analyses, axial clustering and correlation analysis. The result is a sensitive and unbiased assessment of the significant alignment of cell orientations in 3D, compared with a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…Previous work showed that cardiomyocytes at E13.5 undergo primarily parallel OCD based on IFS (Le Garrec et al, 2013), which is consistent with the heart morphogenesis at E13.5, a stage in which trabecular formation is already completed and the heart undergoes expansion. Hence, a high percentage of parallel OCD would be expected.…”
Section: Discussionsupporting
confidence: 82%
“…Previous work showed that cardiomyocytes at E13.5 undergo primarily parallel OCD based on IFS (Le Garrec et al, 2013), which is consistent with the heart morphogenesis at E13.5, a stage in which trabecular formation is already completed and the heart undergoes expansion. Hence, a high percentage of parallel OCD would be expected.…”
Section: Discussionsupporting
confidence: 82%
“…Previously Le Garrec et al demonstrated that myocardial cell division is oriented with a planar bias in embryonic mouse hearts (Le Garrec et al, 2013). We therefore examined E8.5 embryos (prior to the onset of trabeculation) to determine whether luminal myocardial cells displayed oriented cell division relative to the axis of polarity defined by the heart lumen.…”
Section: Resultsmentioning
confidence: 99%
“…It is tempting to speculate that regional polarization of cardiomyoctes combined with specific coordinated movement of regionalized cells results in organ-intrinsic heart looping. Corroborating such a mechanism are recent studies demonstrating that various cell lines exhibit intrinsic left-right polarity 33,34,44 , whereas elegant imaging analyses have demonstrated regionalized cell polarity coordination in the mouse heart during development 45 .…”
Section: Discussionmentioning
confidence: 99%